Characterization of reactive oxygen species in diaphragm. (23rd November 2014) - Zuo, L.; Best, T. M.; Roberts, W. J.; Diaz, P. T.; Wagner, P. D.
Abstract Reactive oxygen species (ROS) exist as natural mediators of metabolism to maintain cellular homeostasis. However, ROS production may significantly increase in response to environmental stressors, resulting in extensive cellular damage. Although several potential sources of increased ROS have been proposed, exact mechanisms of their generation have not been completely elucidated. This is particularly true for diaphragmatic skeletal muscle, the key muscle used for respiration. Several experimental models have focused on detection of ROS generation in rodent diaphragm tissue under stressful conditions, including hypoxia, exercise, and heat, as well as ROS formation in single myofibres. Identification methods include direct detection of ROS with confocal or fluorescent microscopy and indirect detection of ROS through end product analysis. This article explores implications of ROS generation and oxidative stress, and also evaluates potential mechanisms of cellular ROS formation in diaphragmatic skeletal muscle.